What consumers want: a study into consumer preferences and perceptions of destination management websites. - Chia, Germaine Su Fern. (2008)
Destination Management Organizations (DMOs) are generally semi-public but autonomous tourism organizations involving a partnership with both private sector and regional and or local authorities, aimed at marketing and promoting destinations for (mainly) tourism purposes. In recent years, to achieve greater marketing effectiveness, DMOs have established websites that primarily serve to provide relevant information to online consumers regarding the destination areas that they feature.